Assessment of the Kid Production Traits of Kacang Goat under Smallholders Production System - Sodiq, A; Priyono, A; Tawfik, ES (ANIMAL PRODUCTION, 2010)
The main objectives of this study were to assess the influence of environmental (non-genetic) factors on kid production traits of Kacang goat under smallholders production system. The study was conducted at the Kacang goat smallholders, located at the centre of Kacang goat in Gundi subdistric, Purwodadi regency, Central Java. The kid production traits evaluated are birth weight, weaning weight, and growth rate till weaning. The environmental factors assessed were: sex (male, female), type of birth (singles, twins, triplets) and damâs parity (1-7). Data were analysed statistically according to the analysis of variance procedure using the General Linear Model (GLM). Least squares analysis revealed that damâs parity, birth type, and sex of kid were significant sources of variation for birth and weaning weight and pre weaning growth in Kacang kids. The average birth weight, weaning weight and pre weaning growth of males (2.07Â±0.02 kg;Â  10.457Â±0.1 kg; 69.35Â±0.73 g/d) were found to be higher than females (1.95Â±0.02 kg; 9.15Â±0.09 kg; 60.73Â±0.71 g/d). Kid production traits increased with parity, with the largest values at the fourth parity and then slightly decreased thereafter.Â  The average male and female birth weight (2.18+0.03 kg; 2.02+0.03 kg), weaning weight (10.72+0.11 andÂ  9.39+0.13 kg) and pre weaning growth (71.63+0.79 andÂ  62.21+0.96 g/d ) of single kids were heavier than twins, and triplets indicating the influence of the mothering ability of doe. It was recommended, the farmers should consider maternal ability for improvement of weaning weight and growth rate of Kacang kids. (Animal Production 12(2): 111-116 (2010)Key Words: Kacang goat, kid production, birth weight, weaning weight, growth rate